Evaluación Del Efecto De Extracto De Chenopodium Ambrosioides Para El Control De Parásitos Gastrointestinales En Ovinos Y Caprinos De La Granja San Pedro (Uan Sede Usme) - Cruz León, Nicole Tatiana; Acosta Ávila, Nicole Andrea; Cáceres Martínez, Laura Daniela; Rodríguez Hormaza, Sthefania (Universidad Antonio Nariño, 2023)
Sheep and goats are animals that over time have been standing out for their ability to offer a wide variety of products such as meat and milk of great nutritional value, as well as important leathers and wool at an artisanal and industrial level. However, the systems require a high demand to guarantee the quality of life and the health condition of these animals, which is why aspects such as nutrition and health must be considered, mainly in related to foot diseases, metabolic diseases, infectious diseases and parasitic diseases; the latter is currently of great importance due to the high susceptibility of sheep and goats to parasites and resistance problems anthelmintic that is increasing due to the misuse of chemical products. (Waller, 1997).